Comparison of Culprit Artery Patency Between Diabetic and Non-Diabetic Patients Undergoing Thrombolysis with Streptokinase for ST Elevation Myocardial Infarction - Shrestha, Manoj; Bhusal, Pramod; Pradhan, Manohar (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Myocardial Infraction is the leading cause of mortality and mortality globally. Thrombolysis with streptokinase is well established therapeutic intervention in Myocardial Infraction. Timely intervention with adequate myocardial reperfusion is associated with better clinical outcome whereas failed reperfusion due to incomplete or non-reopening of culprit artery is associated with complications. This study aims to compare diabetic and non-diabetic patients with acute myocardial infraction in term is culprit artery patency. Methods This analytical cross-sectional study was carried out in Cardiology Department, Collage of Medical Sciences, Bharatpur from 1st June 2023 to 30th October 2023. Total 80 patients with acute Myocardial Infarction were enrolled in the study. Blood sugar level and twelve leads ECG of each patients were recorded before giving intravenous 1.5 million units of streptokinase over one hour for acute ST elevation myocardial infarction. Coronary angiogram was done after 24 hours of thrombolysis. Patency of the culprit artery was assessed in each patients and compared between diabetics and non-diabetics. Results The study included 57.5 % (n=46) male and 42.5 % (n=34) female patients. Mean random blood sugar level was 160.87 ±40.8 mg/dl. Mean age of the study population was 52.9 ±10.8 years. 40 % (n= 32) of patients were diabetics. The percentage of culprit artery patency was lower in diabetic patients as compared to non-diabetic patients (43.75 % vs 75%). Conclusions Among both male and female patients the success of thrombolysis in term of culprit artery patency was higher in non-diabetic patients as compared to diabetic patients.